Major Security Threats and Attacks that Facing Cloud Computing with the Main Defence Strategies - Safhi, Abdullah; Al-Zahrani, Adel; Mubaraki, Aisha (Communications in Mathematics and Applications, 2022)
Cloud Computing (Cloud) enables ubiquitous network access to a pool of shared and configurable resources. It is based on shared services and infrastructure convergence. Cloud computing offers a slew of advantages, including the ability to store large amounts of data and a variety of services, as well as addressing the issue of scarce resources and lowering service costs. Regardless of its benefits, the shift from local to remote computing has created a slew of security concerns and challenges for both consumer and provider. Addressing and evaluating cloud computing challenges is critical. Thus, by discussing cloud computing challenges alongside available and potential solutions, users, developers, and businesses can identify pertinent and timely responses to specific threats, resulting in the best possible cloud computing-based services. The purpose of this article is to discuss the inherent difficulties associated with cloud computing and some critical solutions for overcoming them. This article extracted and analyzed seminal papers in order to contribute to the corpus of literature by highlighting several critical challenges in the cloud computing domain and shedding light on how these challenges affect a variety of domains, including users, sites, and business. The most frequently mentioned challenges include data loss, data breaches, account or service hijacking, insecure interfaces and APIs, malicious insiders, insufficient due diligence, abusive cloud service use, shared technology issues, unknown risk profile, identity theft, business model changes, lock-in, cryptography, cloud data recycling, malware, and untrusted computing. This paper addressed these issues by incorporating previously discovered solutions. There has been discussion of the implications for both researchers and practitioners.